2023
DOI: 10.1177/03331024231174855
|View full text |Cite
|
Sign up to set email alerts
|

What do patients’ efficacy and tolerability ratings of acute migraine medication tell us? Cross-sectional data from the DMKG Headache Registry

Abstract: Background Most migraine patients need an effective acute medication. Real-world data can provide important information on the performance of acute migraine medication in clinical practice. Methods We used data from the German Migraine and Headache Society Headache Registry, where patients rate efficacy and tolerability of and satisfaction with each of their acute headache medications. Results A total of 1756 adult migraine patients (females: 85%, age: 39.5 ± 12.8 years, headache days per month: 13.5 ± 8.1) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Also, there is no way to know if patients observed the rules of early dosing and treating several attacks before declaring failure of a specific triptan. Regarding dosages, our previous results show that triptan underdosing is very rare in the present sample [ 16 ]. Nonetheless, choice of a low vs. high dose within the range of recommended dosages might affect triptan efficacy and tolerability.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Also, there is no way to know if patients observed the rules of early dosing and treating several attacks before declaring failure of a specific triptan. Regarding dosages, our previous results show that triptan underdosing is very rare in the present sample [ 16 ]. Nonetheless, choice of a low vs. high dose within the range of recommended dosages might affect triptan efficacy and tolerability.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have reported that triptan non-responders have more severe migraine (higher frequency and intensity, more accompanying symptoms, higher disability) than triptan responders [ 1 , 15 ], and a previous DMKG Registry analysis showed that migraine patients with higher headache frequency have lower acute medication efficacy [ 16 ]. The present data expand these results, showing that migraine severity (headache and severe headache frequency, a chronic migraine diagnosis, headache intensity) and associated disability (MIDAS) further increased with increasing level of triptan failure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One of the fundamental goals of migraine prevention is to improve the response to acute treatment. The assessment of patient satisfaction with acute treatment is of particular importance in clinical practice because of its strong association with migraine-related disability [ 18 20 ]. However, this objective remains underexplored, even in the context of randomized controlled trials and real-world studies examining CGRP-mAbs, which focused more on acute medication intake than on their effectiveness [ 3 , 4 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typische Prädiktoren für eine schlechtere Response auf CGRP-Antikörper sind das Vorliegen einer chronischen Migräne, eines Medikamentenübergebrauchs und einer Depression [17]. Auch die Migräne-Akuttherapie mit Triptanen oder Nicht-Opioid-Analgetika ist bei häufigeren Kopfschmerzen signifikant weniger wirksam [18].…”
Section: Multiple Komorbiditätenunclassified